IRF and STAT Transcription Factors - From Basic Biology to Roles in Infection, Protective Immunity, and Primary Immunodeficiencies - Mogensen, Trine H. (Frontiers in Immunology, 2019)
The induction and action of type I interferon (IFN) is of fundamental importance in human immune defenses towards microbial pathogens, particularly viruses. Basic discoveries within the molecular and cellular signaling pathways regulating type I IFN induction and downstream actions have shown the essential role of the IFN regulatory factor (IRF) and the signal transducer and activator of transcription (STAT) families, respectively. However, the exact biological and immunological functions of these factors have been most clearly revealed through the study of inborn errors of immunity and the resultant infectious phenotypes in humans. The spectrum of human inborn errors of immunity caused by mutations in IRFs and STATs has proven very diverse and ranges from herpes simplex encephalitis (HSE) and severe influenza in IRF3- and IRF7/IRF9 deficiency, respectively, to conditions predisposing to mycobacterial infections in Mendelian susceptibility to mycobacterial infection (MSMD) in STAT1 deficiency, through disseminated measles infection associated with STAT2 deficiency, and finally to staphylococcal abscesses and chronic mucocutaneous candidiasis (CMC) classically described with Hyper-IgE syndrome (HIES) syndrome in the case of STAT3 deficiency. More recently, increasing focus has been on aspects of autoimmunity and autoinflammation playing an important part in many primary immunodeficiency diseases (PID)s, as exemplified by STAT1 gain-of-function causing CMC and autoimmune thyroiditis, as well as a recently described autoinflammatory syndrome with hypogammaglobulinemia and lymphoproliferation as a result of STAT3 gain-of-function. Here I review the infectious, inflammatory, and autoimmune disorders arising from mutations in IRF and STAT transcription factors in humans, highlightning the underlying molecular mechanisms and immunepathogenesis as well as the clinical/therapeutic perspectives of these new insights.